A super durable dual-liquid grouting material
By using specific components A and B ratios in the double-liquid grouting material, combining ultrafine zinc phosphate, ferrosilicon powder, zinc oxide powder, oxalate powder and sepiolite loading curing agent and other materials, the solution is solved The cement-water glass double-liquid grouting material has low curing strength and insufficient durability, and a high-strength and ultra-durability double-liquid grouting material has been achieved.
Patent Information
- Application Number
- CN202411686920.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing cement-water glass double-liquid grouting materials have problems with low curing strength and insufficient durability, especially the shrinkage caused by water glass during the curing process has great damage to the strength, and the dissolution of solidified sodium ions affects durability.
The ultra-durable double-liquid grouting material is used to mix components A and components B at a mass ratio of 1:1.3~2.5. Component A includes sodium water glass solution, ultrafine zinc phosphate, ferrosilicon powder, zinc oxide powder, Oxalate powder and polyether-siloxane copolymer, component B includes cement, sepiolite-supported curing agent, aluminum dihydrogen phosphate, polyhydroxy enhancer and polyether-siloxane copolymer.
The compressive strength and durability of the grouting material are significantly improved, the flowability is good, the settling time is moderate, the cured body maintains a high compressive strength for a long time, and has excellent freeze-thaw resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a super-durable double-liquid grouting material, belonging to the technical field of grouting filling materials. Background Art
[0002] Grouting reinforcement technology is a very mature civil engineering technology, and its application scope covers geotechnical engineering, coal mine reinforcement, road engineering, submarine tunnel engineering and other fields. Grouting reinforcement technology mainly relies on the performance and properties of the grouting material itself to achieve the final application requirements. Therefore, with the continuous expansion of the application scope of grouting reinforcement technology, the requirements for the key performance indicators of grouting materials are constantly increasing. For example, in the reinforcement of fine sand formations, submarine tunnel grouting, heavy-load road repair and reinforcement projects, the performance indicators of grouting materials such as fluidity, strength, durability and impermeability are crucial.
[0003] Grouting materials are generally divided into two categories: organic and inorganic. Organic grouting materials include quality, acrylamide, polyurethane, urea-formaldehyde resin and other organic grouting materials. Due to their high price, poor durability and pollution, their application is limited. Inorganic grouting materials include cement, water glass, cement-water glass, cement clay and other inorganic slurries in single or double liquid form. Because the inorganic series is mainly cement materials, it is low in price, environmentally friendly, has low permeability, high stone body strength and relatively good durability. At the same time, its process and water-stopping performance can be improved by adding admixtures or mineral admixtures. Therefore, it is widely used at home and abroad. Cement-water glass double liquid grouting materials in inorganic grouting materials have excellent fluidity, good pourability and relatively low price. Therefore, the market demand is relatively large and the application fields are relatively wide. However, due to the addition of water glass, there are problems of low curing strength and insufficient durability. During the hardening process and after solidification of water glass, it will produce large shrinkage, which will cause great damage to the solidification strength. In addition, the sodium ions contained in the water glass will gradually dissolve in the solidified slurry. This process has a great negative impact on the durability of the reinforced layer of the solidified slurry. Although the addition of cement can improve the problem of decreased durability to a certain extent, it cannot fundamentally avoid this inherent defect caused by water glass. Therefore, the durability of cement-water glass two-liquid grouting materials has always been the focus of research in the industry.
[0004] Chinese patent CN105272030A discloses a double liquid grouting material with good durability and no environmental pollution. It uses a mixture of amorphous calcium aluminate, gypsum and water, which has a fast dissolution rate and can react quickly with silicate cement, and its reaction product is not easily dissolved, and the mixture is made of amorphous calcium aluminate, gypsum and water, mud A, to replace water glass; and a mixture of silicate cement, gypsum and water, mud B, to form a double liquid, which can overcome the shortcomings of water glass and become a double liquid grouting material with good durability and no environmental pollution. The patent replaces the use of water glass with a mixture of amorphous calcium aluminate, gypsum and water. Strictly speaking, it is not a cement-water glass double liquid grouting material. Moreover, the patent does not clearly explain how the fluidity of the mixture of amorphous calcium aluminate, gypsum and water compares with water glass. Generally speaking, the fluidity of the grouting material system involving water glass is better than other alternative materials.
[0005] Chinese patent CN117800696A discloses a fly ash modified two-liquid grouting material, including group A materials, group B materials and disodium hydrogen phosphate; group A materials include cement, fly ash and water, the weight of fly ash is 0 to 60 parts, and the weight of cement, fly ash and water is determined by the following steps: Step 1: According to the formula: water-cement ratio = weight of water / (weight of cement + weight of fly ash), the weight ratio between water and cement is calculated, and the water-cement ratio of group A materials is 0.6 to 0.8; Step 2: when the weight of fly ash is greater than 0, the amount of fly ash added is 45 to 55% of the total weight of fly ash and cement; group B materials include water glass, and the Baume degree of water glass in the prepared fly ash modified two-liquid grouting material is 40 to 53; the weight of disodium hydrogen phosphate is 0 to 3% of the total weight of cement and fly ash. The fly ash modified double-liquid grouting material obtained by this patent has a maximum compressive strength of only 18.7MPa, and a strength loss rate of up to 9.1% after 28 days, and its durability is relatively poor.
[0006] From the above discussion, it can be seen that the current cement-water glass two-liquid grouting material still has significant disadvantages of low strength and poor durability. Therefore, the development of high-strength and ultra-durable two-liquid grouting material is of great practical significance. Summary of the invention
[0007] In view of the deficiencies in the above-mentioned prior art, the present invention provides a super-durable double-liquid grouting material to achieve the following invention objectives: to prepare an organic-inorganic composite grouting material with good fluidity and high strength.
[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0009] A super durable double liquid grouting material, the super durable double liquid grouting material is composed of component A and component B, and during grouting, component A and component B are mixed in a mass ratio of 1:1.3-2.5;
[0010] The specific formula of the component A is, in parts by weight:
[0011] 90~150 parts of sodium water glass solution,
[0012] 2~11 parts of superfine zinc phosphate,
[0013] 3~15 parts of ferrosilicon powder,
[0014] 1~3 parts of zinc oxide powder,
[0015] 3~10 parts of oxalate powder,
[0016] 0.5~2 parts of sodium lignin sulfonate,
[0017] Polyether-siloxane copolymer 0.1~0.4 parts,
[0018] 25~65 parts of deionized water;
[0019] In the sodium water glass solution, the mass fraction of sodium metasilicate is 10-40wt%, and the modulus of sodium metasilicate is 1-3.5;
[0020] The particle size of the ultrafine zinc phosphate is 600-1000 mesh;
[0021] The particle size of the ferrosilicon powder is 500-1000 mesh;
[0022] The particle size of the zinc oxide powder is 500-1200 mesh;
[0023] The particle size of the oxalate powder is 800-1200 mesh;
[0024] The oxalate is one of aluminum oxalate, iron oxalate, magnesium oxalate and zinc oxalate;
[0025] The specific formula of the B component is, in parts by weight:
[0026] 80~140 parts of cement,
[0027] 15~40 parts of sepiolite loaded curing agent,
[0028] 3~10 parts of aluminum dihydrogen phosphate,
[0029] 1~5 parts of polyhydroxy enhancer,
[0030] Polyether-siloxane copolymer 0.1~0.4 parts,
[0031] 55~110 parts of deionized water;
[0032] The cement is ordinary Portland cement 42.5;
[0033] The polyhydroxy enhancer is one of tris(2-hydroxyethyl)isocyanurate triacrylate and bis(hydroxyethyl)sulfone;
[0034] The following are further improvements to the above technical solution:
[0035] Step 1, preparation of sepiolite-loaded curing agent
[0036] The sepiolite is dried at 110-140°C for 2-5 hours, cooled to room temperature, and then placed in a completely dry and water-free vacuum-sealed impregnation kettle. The vacuum is continuously drawn to maintain the pressure in the kettle at -0.096-0.1MPa. After maintaining the negative pressure for 20-30 hours, the liquid amide is sucked into the reaction kettle by the negative pressure in the kettle. The minimum amount of liquid amide sucked is when all the sepiolite in the kettle is immersed. After reaching the minimum amount of liquid amide, the kettle is left standing at a constant temperature for 24-30 hours in a sealed state. The sepiolite is transferred to a high-speed centrifuge and centrifuged. The separated sepiolite is put into a clean impregnation kettle again, and then an aqueous solution of water-soluble silicon phosphate is added to the impregnation kettle, with the minimum amount added being enough to completely immerse the sepiolite in the kettle. After standing and impregnating for 15 to 24 hours, stirring is started, and the stirring rate is controlled at 300 to 600 rpm. After stirring for 15 to 30 minutes, the sepiolite is continued to stand and impregnate for 15 to 24 hours, and then filtered and separated. The filtered solid is the sepiolite-loaded curing agent.
[0037] The particle size of the sepiolite is 30-3000 nm;
[0038] The liquid amide is one of diethanolamide and formamide;
[0039] The aqueous solution of water-soluble silicon phosphate, wherein the mass fraction of water-soluble silicon phosphate is 15-30wt%.
[0040] Step 2: Preparation of component A
[0041] According to the specific formula of component A in parts by weight, deionized water, sodium lignin sulfonate, polyether-siloxane copolymer, sodium water glass solution, ultrafine zinc phosphate, ferrosilicon powder, zinc oxide powder and oxalate powder are placed in a high-speed stirring mixing kettle, the stirring rate is controlled at 5000-9000 rpm, and after high-speed stirring and mixing for 14-20 hours, a mixed slurry is obtained, and after vacuum degassing, component A is obtained.
[0042] Step 3: Preparation of component B
[0043] According to the specific formula of component B in parts by weight, deionized water, polyether-siloxane copolymer, polyhydroxy enhancer, aluminum dihydrogen phosphate, sepiolite-loaded curing agent and cement are placed in a high-speed stirring mixing kettle, the stirring rate is controlled at 6000-9500 rpm, and after high-speed stirring and mixing for 10-16 hours, a mixed slurry is obtained, and after vacuum degassing, component B is obtained.
[0044] Compared with the prior art, the present invention achieves the following beneficial effects:
[0045] 1. The sepiolite-loaded curing agent prepared by the present invention can effectively control the curing rate of the double-liquid grouting material, greatly improve the compressive strength and durability of the grouting material after curing. The surface and outer surface of the inner hole wall of the sepiolite are rich in active hydroxyl groups. During the negative pressure adsorption process, diethanolamide and formamide, two amide substances that are very easy to form hydrogen bonds, enter the inner holes of the sepiolite under the drive of vacuum negative pressure. The liquid amide closest to the inner hole wall surface forms hydrogen bonds with the hydroxyl groups on the hole wall surface. It is firmly adsorbed on the pore walls inside the sepiolite. Similarly, the outer surface of the sepiolite will also adsorb liquid amide due to hydrogen bonding. When the sepiolite adsorbed with liquid amide inside and outside is placed in an aqueous solution of water-soluble silicon phosphate, the liquid amide carries a highly negatively charged lone electron pair due to the presence of a primary amine molecular structure. This highly negatively charged lone electron pair is easy to react with the water-soluble silicon phosphate to form a complex containing an amino-like molecular structure. This complexing effect causes the surface and outer surface of the pore walls inside the sepiolite to adsorb liquid amide. A large amount of water-soluble silicon phosphate, during the curing process of the two-liquid grouting material, with the reduction of water in the slurry reaction system and the dissociation of the above-mentioned complex caused by the reaction heat, the water-soluble silicon phosphate adsorbed on the surface of the pore wall inside the sepiolite will slowly overflow from the inner pores of the sepiolite, and at the same time, the water-soluble silicon phosphate adsorbed on the outer surface of the sepiolite will also be freed into the reaction system due to the decomplexation of the complex. The above water-soluble silicon phosphate freed from the inside and outside of the sepiolite will promote the cross-linking and curing reaction of water glass. This method of slowly promoting and gradually releasing the curing agent by water loss and reaction heat can control the speed of the cross-linking gel reaction of water glass, so that the grouting material maintains a certain fluidity for a considerable period of time, and improves the fluidity of the two-liquid grouting material. Secondly, the cross-linking and curing reaction is carried out around the central site of sepiolite, and sepiolite is in the central position of the cross-linking and curing network, which will further promote and increase the reinforcing effect of sepiolite on the grouting material solidification body, greatly improving the compressive strength and compressive strength durability and freeze-thaw resistance of the final solidification body;
[0046] 2. The three ultrafine powdery substances of ultrafine zinc phosphate, ferrosilicon powder and zinc oxide powder added in the present invention will generate a certain amount of sodium hydroxide during the solidification process of sodium water glass after the double liquid grouting material is mixed and poured, resulting in a microscopic local strong alkaline environment. This strong alkaline environment will promote the dissolution of the three substances of ultrafine zinc phosphate, ferrosilicon powder and zinc oxide, and dissolve iron ions and zinc ions. The iron ions and zinc ions will replace the sodium ions in the solidification network of sodium water glass to generate more stable zinc silicate and iron silicate, forming a three-dimensional cross-linked solidification network structure of water glass containing a reticular zinc silicate complex and an iron silicate complex. This more dense cross-linked structure can significantly enhance the compressive strength of the grouting material after solidification and the durability of the compressive strength;
[0047] 3. The oxalate powders of aluminum oxalate, iron oxalate, magnesium oxalate and zinc oxalate added in the present invention are all solid powders that are difficult to dissolve or slightly soluble in water. The particle size of these powders is limited to 800-1200 meshes, which are micron-sized powders and can be easily evenly dispersed in the slurry. In addition, the amount added is relatively small, which has almost no effect on the fluidity of the slurry. Therefore, there is no negative effect on the grouting construction process of the double-liquid grouting material. The addition of these oxalates mainly serves to improve the compressive strength and durability of the solidified body of the grouting material. The working principle is as follows: the decrease in the compressive strength of the solidified body of the grouting material is mainly due to the fact that the solidified network formed after the water glass solidifies contains a considerable amount of sodium ions. The sodium ions are very easy to absorb moisture and dissolve. During the dissolution process, the sodium ions will combine with hydroxide to form sodium hydroxide and dissolve in water. Finally, they are gradually dissolved from the solidified network with water-containing moisture in the form of sodium hydroxide compounds, forming defects and holes inside the solidified body. Over the years, Under the condition of dissolution accumulation, the slurry solidification body collapses and shrinks, and loses its mechanical structural support. In the strong alkaline microscopic local environment formed by the moisture absorption of sodium ions to generate sodium hydroxide, the weak dissolution of the four oxalates of aluminum oxalate, iron oxalate, magnesium oxalate and zinc oxalate will generate corresponding gel-like hydroxides such as aluminum hydroxide, iron hydroxide, magnesium hydroxide and zinc hydroxide. The corresponding anion oxalate will form a more difficult to dissolve calcium oxalate precipitate with the calcium ions dissociated from the cement solidification network in the solidification body. The calcium oxalate precipitate and the gel-like hydroxide mentioned above will block the microscopic channels for the dissolution of sodium ions, greatly reducing or even preventing the dissolution of sodium ions from the network body after the water glass solidification. This fundamentally avoids the problem of collapse and shrinkage of the slurry solidification body caused by the long-term dissolution accumulation, so that the double liquid grouting material obtained by the present invention has extremely excellent durability.
[0048] 4. The aluminum dihydrogen phosphate added in the present invention, firstly, utilizes the ionized dihydrogen phosphate in the alkaline environment formed in the solidification process of water glass. Due to the fluctuation of pH value, the dihydrogen phosphate gradually ionizes and releases hydrogen ions. These hydrogen ions can play an acid catalytic role and can improve the solidification rate of water glass. In addition, the ionized aluminum ions can replace the sodium ions in the network body during the solidification of water glass to form a network body, thereby reducing the content of sodium ions in the solidified cross-linked network. This also reduces the decrease in compressive strength of the solidified body of the double-liquid grouting material due to the dissolution of sodium ions during the subsequent service period to a certain extent;
[0049] 5. The polyhydroxy reinforcing agent added in the present invention, tris(2-hydroxyethyl)isocyanuric acid triacrylate and bis(hydroxyethyl)sulfone, contains a hydroxyethyl structure. During the curing process of water glass, the hydroxyl groups on the hydroxyethyl structure can be adsorbed on the surface of silica gel particles, hindering the rapid increase of the particles and promoting the refinement of the particle size of the particles. In this way, the finer the particles, the more bonding points and cross-linking points per unit volume of silica gel, the denser the cross-linking network, and the compressive strength of the slurry after curing will be greatly improved.
[0050] 6. The ultra-durable two-liquid grouting material obtained by the present invention has a fluidity of 8 to 10 seconds, an initial setting time of 30 to 37 minutes, a final setting time of 48 to 55 minutes, a compressive strength of 18.9 to 20.8 MPa at 3 days, 22.7 to 24.6 MPa at 7 days, 25.1 to 27.0 MPa at 28 days, and 24.3 to 26.2 MPa at 365 days, and a freeze-thaw expansion rate of 0.1 to 0.2% after 10 freeze-thaw cycles. DETAILED DESCRIPTION
[0051] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0052] Example 1: A super durable dual-liquid grouting material
[0053] Step 1, preparation of sepiolite-loaded curing agent
[0054] The sepiolite is dried at 130° C. for 4 hours, cooled to room temperature, and then placed in a completely dry and water-free vacuum sealed impregnation kettle, and vacuum is continuously drawn to maintain the pressure in the kettle at -0.098 MPa. After maintaining the negative pressure for 26 hours, the liquid amide is sucked into the reaction kettle by relying on the negative pressure in the kettle. The amount of liquid amide sucked is the minimum amount of the sepiolite in the kettle being completely immersed. After reaching the minimum amount of the liquid amide, the sepiolite in the kettle is allowed to stand at a constant temperature for 29 hours in a sealed state, and then the sepiolite in the kettle is transferred to a high-speed centrifuge for centrifugal separation. The separated sepiolite is put into a clean impregnation kettle again, and then an aqueous solution of water-soluble silicon phosphate is added to the impregnation kettle. The amount of the added amount is the minimum amount of the sepiolite in the kettle being completely immersed. After standing and impregnating for 18 hours, stirring is started, and the stirring rate is controlled at 500 rpm. After stirring for 20 minutes, the kettle is allowed to stand and impregnate for 22 hours, and then filtered and separated. The filtered solid is the sepiolite-loaded curing agent.
[0055] The particle size of the sepiolite is 100 nm;
[0056] The liquid amide is diethanolamide;
[0057] The aqueous solution of water-soluble silicon phosphate, wherein the mass fraction of water-soluble silicon phosphate is 19wt%.
[0058] Step 2: Preparation of component A
[0059] The specific formula of the component A is, in parts by weight:
[0060] 110 parts of sodium water glass solution,
[0061] 8 parts of superfine zinc phosphate,
[0062] 6 parts of ferrosilicon powder,
[0063] 2 parts zinc oxide powder,
[0064] 5 parts of oxalate powder,
[0065] 1 part of sodium lignin sulfonate,
[0066] 0.2 parts of polyether-siloxane copolymer,
[0067] 50 parts of deionized water;
[0068] In the sodium water glass solution, the mass fraction of sodium metasilicate is 30wt%, and the modulus of sodium metasilicate is 2;
[0069] The particle size of the ultrafine zinc phosphate is 800 mesh;
[0070] The particle size of the ferrosilicon powder is 800 mesh;
[0071] The particle size of the zinc oxide powder is 1000 mesh;
[0072] The particle size of the oxalate powder is 1000 mesh;
[0073] The oxalate is aluminum oxalate;
[0074] According to the specific formula of component A in parts by weight, deionized water, sodium lignin sulfonate, polyether-siloxane copolymer, sodium water glass solution, ultrafine zinc phosphate, ferrosilicon powder, zinc oxide powder and oxalate powder are placed in a high-speed stirring mixing kettle. The stirring rate is controlled to 8000 rpm. After high-speed stirring and mixing for 18 hours, a mixed slurry is obtained. After vacuum degassing, component A is obtained.
[0075] Step 3: Preparation of component B
[0076] The specific formula of the B component is, in parts by weight:
[0077] 120 parts of cement,
[0078] 30 parts of sepiolite loaded curing agent,
[0079] 7 parts of aluminum dihydrogen phosphate,
[0080] 4 parts of polyhydroxy enhancer,
[0081] 0.2 parts of polyether-siloxane copolymer,
[0082] 90 parts of deionized water;
[0083] The cement is ordinary Portland cement 42.5;
[0084] The polyhydroxy enhancer is tris(2-hydroxyethyl)isocyanurate triacrylate;
[0085] According to the specific formula of component B in parts by weight, deionized water, polyether-siloxane copolymer, polyhydroxy enhancer, aluminum dihydrogen phosphate, sepiolite-loaded curing agent and cement are placed in a high-speed stirring mixing kettle. The stirring rate is controlled to 8500 rpm. After high-speed stirring and mixing for 12 hours, a mixed slurry is obtained. After vacuum degassing, component B is obtained.
[0086] Example 2: A super durable dual-liquid grouting material
[0087] Step 1, preparation of sepiolite-loaded curing agent
[0088] The sepiolite is dried at 110° C. for 2 hours, cooled to room temperature, and then placed in a completely dry and water-free vacuum sealed impregnation kettle, and vacuum is continuously drawn to maintain the pressure in the kettle at -0.096 MPa. After maintaining the negative pressure for 20 hours, the liquid amide is sucked into the reaction kettle by relying on the negative pressure in the kettle. The amount of liquid amide sucked is the minimum amount of the sepiolite in the kettle being completely immersed. After reaching the minimum amount of the liquid amide, the sepiolite in the kettle is allowed to stand at a constant temperature for 24 hours in a sealed state, and then the sepiolite in the kettle is transferred to a high-speed centrifuge for centrifugal separation. The separated sepiolite is put into a clean impregnation kettle again, and then an aqueous solution of water-soluble silicon phosphate is added to the impregnation kettle, and the amount added is the minimum amount of the sepiolite in the kettle being completely immersed. After standing and impregnating for 15 hours, stirring is started, and the stirring rate is controlled at 300 rpm. After stirring for 15 minutes, the kettle is allowed to stand and impregnate for another 15 hours, and then filtered and separated. The filtered solid is the sepiolite-loaded curing agent.
[0089] The particle size of the sepiolite is 30 nm;
[0090] The liquid amide is formamide;
[0091] The aqueous solution of water-soluble silicon phosphate, wherein the mass fraction of water-soluble silicon phosphate is 15wt%.
[0092] Step 2: Preparation of component A
[0093] The specific formula of the component A is, in parts by weight:
[0094] 90 parts of sodium water glass solution,
[0095] 2 parts of superfine zinc phosphate,
[0096] 3 parts of ferrosilicon powder,
[0097] 1 part zinc oxide powder,
[0098] 3 parts oxalate powder,
[0099] 0.5 parts of sodium lignin sulfonate,
[0100] 0.1 part of polyether-siloxane copolymer,
[0101] 25 parts of deionized water;
[0102] In the sodium water glass solution, the mass fraction of sodium metasilicate is 10wt%, and the modulus of sodium metasilicate is 1;
[0103] The particle size of the ultrafine zinc phosphate is 600 mesh;
[0104] The particle size of the ferrosilicon powder is 500 mesh;
[0105] The particle size of the zinc oxide powder is 500 mesh;
[0106] The particle size of the oxalate powder is 800 mesh;
[0107] The oxalate is ferric oxalate;
[0108] According to the specific formula of component A in parts by weight, deionized water, sodium lignin sulfonate, polyether-siloxane copolymer, sodium water glass solution, ultrafine zinc phosphate, ferrosilicon powder, zinc oxide powder and oxalate powder are placed in a high-speed stirring mixing kettle. The stirring rate is controlled to 5000 rpm. After high-speed stirring and mixing for 14 hours, a mixed slurry is obtained. After vacuum degassing, component A is obtained.
[0109] Step 3: Preparation of component B
[0110] The specific formula of the B component is, in parts by weight:
[0111] 80 parts of cement,
[0112] 15 parts of sepiolite loaded curing agent,
[0113] 3 parts of aluminum dihydrogen phosphate,
[0114] 1 part of polyhydroxy enhancer,
[0115] 0.1 part of polyether-siloxane copolymer,
[0116] 55 parts of deionized water;
[0117] The cement is ordinary Portland cement 42.5;
[0118] The polyhydroxy enhancer is bis(hydroxyethyl)sulfone;
[0119] According to the specific formula of component B in parts by weight, deionized water, polyether-siloxane copolymer, polyhydroxy enhancer, aluminum dihydrogen phosphate, sepiolite-loaded curing agent and cement are placed in a high-speed stirring mixing kettle. The stirring rate is controlled to 6000 rpm. After high-speed stirring and mixing for 10 hours, a mixed slurry is obtained. After vacuum degassing, component B is obtained.
[0120] Example 3: A super durable dual-liquid grouting material
[0121] Step 1, preparation of sepiolite-loaded curing agent
[0122] The sepiolite is dried at 140° C. for 5 hours, cooled to room temperature, and then placed in a completely dry and water-free vacuum sealed impregnation kettle, and vacuum is continuously drawn to maintain the pressure in the kettle at -0.1 MPa. After the negative pressure is maintained for 30 hours, the liquid amide is sucked into the reaction kettle by relying on the negative pressure in the kettle, and the amount of liquid amide sucked is the minimum amount when all the sepiolite in the kettle is immersed. After reaching the minimum amount, the sepiolite in the kettle is allowed to stand at a constant temperature for 30 hours in a sealed state, and then the sepiolite in the kettle is transferred to a high-speed centrifuge for centrifugal separation. The separated sepiolite is put into a clean impregnation kettle again, and then an aqueous solution of water-soluble silicon phosphate is added to the impregnation kettle, and the amount added is the minimum amount when all the sepiolite in the kettle is immersed. After standing and impregnating for 24 hours, stirring is started, and the stirring rate is controlled at 600 rpm. After stirring for 30 minutes, the kettle is allowed to stand and impregnate for another 24 hours, and then filtered and separated. The filtered solid is the sepiolite-loaded curing agent;
[0123] The particle size of the sepiolite is 3000nm;
[0124] The liquid amide is diethanolamide;
[0125] The aqueous solution of water-soluble silicon phosphate, wherein the mass fraction of water-soluble silicon phosphate is 30wt%.
[0126] Step 2: Preparation of component A
[0127] The specific formula of the component A is, in parts by weight:
[0128] 150 parts of sodium water glass solution,
[0129] 11 parts of superfine zinc phosphate,
[0130] 15 parts of ferrosilicon powder,
[0131] 3 parts zinc oxide powder,
[0132] 10 parts oxalate powder,
[0133] 2 parts of sodium lignin sulfonate,
[0134] 0.4 parts of polyether-siloxane copolymer,
[0135] 65 parts of deionized water;
[0136] In the sodium water glass solution, the mass fraction of sodium metasilicate is 40wt%, and the modulus of sodium metasilicate is 3.5;
[0137] The particle size of the ultrafine zinc phosphate is 1000 mesh;
[0138] The particle size of the ferrosilicon powder is 1000 mesh;
[0139] The particle size of the zinc oxide powder is 1200 mesh;
[0140] The particle size of the oxalate powder is 1200 mesh;
[0141] The oxalate is magnesium oxalate;
[0142] According to the specific formula of component A in parts by weight, deionized water, sodium lignin sulfonate, polyether-siloxane copolymer, sodium water glass solution, ultrafine zinc phosphate, ferrosilicon powder, zinc oxide powder and oxalate powder are placed in a high-speed stirring mixing kettle. The stirring rate is controlled to 9000 rpm. After high-speed stirring and mixing for 20 hours, a mixed slurry is obtained. After vacuum degassing, component A is obtained.
[0143] Step 3: Preparation of component B
[0144] The specific formula of the B component is, in parts by weight:
[0145] 140 parts of cement,
[0146] 40 parts of sepiolite loaded curing agent,
[0147] 10 parts of aluminum dihydrogen phosphate,
[0148] 5 parts of polyhydroxy enhancer,
[0149] 0.4 parts of polyether-siloxane copolymer,
[0150] 110 parts of deionized water;
[0151] The cement is ordinary Portland cement 42.5;
[0152] The polyhydroxy enhancer is tris(2-hydroxyethyl)isocyanurate triacrylate;
[0153] According to the specific formula of component B in parts by weight, deionized water, polyether-siloxane copolymer, polyhydroxy enhancer, aluminum dihydrogen phosphate, sepiolite-loaded curing agent and cement are placed in a high-speed stirring mixing kettle. The stirring rate is controlled to 9500 rpm. After high-speed stirring and mixing for 16 hours, a mixed slurry is obtained. After vacuum degassing, component B is obtained.
[0154] Example 4: A super durable dual-liquid grouting material
[0155] The operation of step 1 is the same as that of embodiment 1;
[0156] Step 2: Preparation of component A
[0157] The oxalate is zinc oxalate, and the other operations are the same as in Example 1;
[0158] The operation of step 3 is the same as that of embodiment 1.
[0159] Comparative Example 1: Based on Example 1, step 1, preparation of sepiolite-loaded curing agent, is not performed. In step 3, preparation of component B, 30 parts of sepiolite-loaded curing agent are replaced by 30 parts of deionized water. The specific operation is as follows:
[0160] Step 1, preparation of sepiolite-loaded curing agent is not performed;
[0161] The operation of step 2 is the same as that of embodiment 1;
[0162] Step 3: Preparation of component A
[0163] In the specific formula of component A, 30 parts of sepiolite-loaded curing agent were replaced by 30 parts of deionized water, and the other operations were the same as in Example 1.
[0164] Comparative Example 2: Based on Example 1, in step 2, in the preparation of component A, no ultrafine zinc phosphate, ferrosilicon powder, and zinc oxide powder were added, and 8 parts of ultrafine zinc phosphate, 6 parts of ferrosilicon powder, and 2 parts of zinc oxide powder were replaced by 16 parts of deionized water in equal amounts. The specific operation is as follows:
[0165] The operation of step 1 is the same as that of embodiment 1;
[0166] Step 2: Preparation of component A
[0167] 8 parts of ultrafine zinc phosphate, 6 parts of ferrosilicon powder, and 2 parts of zinc oxide powder were replaced by 16 parts of deionized water, and the other operations were the same as in Example 1;
[0168] The operation of step 3 is the same as that of embodiment 1.
[0169] Comparative Example 3: Based on Example 1, in step 2, in the preparation of component A, no oxalate powder was added, and 5 parts of oxalate powder were replaced by 5 parts of deionized water. The specific operation was as follows:
[0170] The operation of step 1 is the same as that of embodiment 1;
[0171] Step 2: Preparation of component A
[0172] The 5 parts of oxalate powder were replaced by 5 parts of deionized water, and the other operations were the same as in Example 1;
[0173] The operation of step 3 is the same as that of embodiment 1.
[0174] Comparative Example 4: Based on Example 1, in step 3, in the preparation of component B, no aluminum dihydrogen phosphate was added, and 7 parts of aluminum dihydrogen phosphate were replaced by 7 parts of deionized water. The specific operation was as follows:
[0175] The operations of steps 1 and 2 are the same as those of Example 1;
[0176] Step 3: Preparation of component B
[0177] 7 parts of aluminum dihydrogen phosphate were replaced by 7 parts of deionized water, and the other operations were the same as in Example 1.
[0178] Comparative Example 5: Based on Example 1, in step 3, in the preparation of component B, no polyhydroxy enhancer is added, and 4 parts of polyhydroxy enhancer are replaced by 4 parts of deionized water in equal amounts. The specific operation is as follows:
[0179] The operations of steps 1 and 2 are the same as those of Example 1;
[0180] Step 3: Preparation of component B
[0181] The 4 parts of polyhydroxy enhancer were replaced by 4 parts of deionized water, and the other operations were the same as in Example 1.
[0182] Performance Testing:
[0183] The super durable two-liquid grouting materials obtained in Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3, 4, and 5 were mixed with component A and component B in a mass ratio of 1:2 for grouting. The fluidity and setting time of the super durable two-liquid grouting materials during grouting, as well as the compressive strength, freeze-thaw expansion rate and other performance indicators of the solidified body after consolidation were tested with reference to the Technical Specification for Building Grouting (GB / T 50082-2009), the Test Code for Cement and Cement Concrete for Highway Engineering (JTGE30-2005), the Technical Code for Grouting Reinforcement of Highway Roadbed and Base (SZ-G-B04-2007) and the Test Code for Stabilized Materials of Inorganic Binders for Highway Engineering (JTGE51-2009). The specific test data are shown in Table 1;
[0184] Table 1
[0185]
[0186] From the data in Table 1, it can be seen that the fluidity of Examples 1-4 is relatively good, the initial setting time is 30-37 minutes, the final setting time is 48-55 minutes, the compressive strength can basically reach 19MPa and above in 3 days, the compressive strength of 7 days and 28 days has been increasing with the increase of time, the compressive strength after 365 days has decreased very little, and the 10 freeze-thaw expansion rates are all below 0.2%; Comparative Example 1 without sepiolite-loaded curing agent, the fluidity is slightly better than that of Example 1, the initial setting time and final setting time are greatly increased, the compressive strength is greatly reduced, and the compressive strength after 365 days is reduced to 9.1MPa, and the 10 freeze-thaw expansion rates are sharply increased to 1.8%, which shows that the sepiolite-loaded curing agent has an effect on the gel and curing speed of water glass. The rate has a very significant effect, which can greatly improve the gel speed and curing speed, and has a crucial effect on improving the compressive strength of the grouting material consolidation body, and also has an extremely critical effect on improving the durability of the compressive strength and the freeze-thaw expansion rate; in Comparative Example 2, ultrafine zinc phosphate, ferrosilicon powder, and zinc oxide powder are not added, and the fluidity is significantly better than that of Example 1, the initial setting time and the final setting time are increased, and the compressive strength from 3 to 28 days has been increasing, but the increase is very small, the compressive strength at 28 days only reaches 18.8MPa, and the compressive strength at 365 days decreases greatly, and the freeze-thaw expansion rate increases to 0.9%, which shows that ultrafine zinc phosphate, ferrosilicon powder, and zinc oxide powder have a certain effect on the fluidity of the slurry, but these three powders have a certain effect on improving the curing rate. It has a certain effect, and it also has a relatively obvious positive effect on improving the compressive strength and durability of compressive strength and improving freeze-thaw resistance; in Example 3, no oxalate powder is added, the fluidity is basically unchanged, the initial setting time and final setting time are slightly increased, and the compressive strength decreases significantly, especially the durability of the compressive strength. The compressive strength after 365 days is more than half lower than that after 28 days. This shows that the most important function of oxalate powder is to improve the durability of the grouting material consolidation body and to maintain the mechanical strength of the consolidation body for a long time; in Example 4, no aluminum dihydrogen phosphate is added, the fluidity is increased to 5s, the initial setting time and final setting time are extended to more than 1 hour, the compressive strength is reduced to below 20MPa, and the durability of the compressive strength is also greatly improved. The freeze-thaw expansion rate increased to 1.1%, which shows that aluminum dihydrogen phosphate can not only improve the curing rate but also greatly improve the compressive strength of the grouting material consolidation body, and at the same time, it also has a considerable effect on the durability of the compressive strength and the freeze-thaw resistance. In Comparative Example 5, no polyhydroxy enhancer was added, the fluidity increased to 4s, the initial setting time and the final setting time increased to the maximum value, the compressive strength decreased significantly, and the compressive strength at 365 days was not reduced too much compared with the compressive strength at 28 days. The freeze-thaw expansion rate increased sharply to 1.5%, which shows that the polyhydroxy enhancer has a very significant effect on improving the curing rate and the compressive strength after curing, and also has a considerable impact on the durability of the compressive strength, especially the freeze-thaw resistance.
[0187] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A super durable double liquid grouting material, characterized in that: The ultra-durable double-liquid grouting material is composed of component A and component B. During grouting, component A and component B are mixed in a mass ratio of 1:1.3-2.5; The specific formula of the component A is, in parts by weight: 90~150 parts of sodium water glass solution, 2~11 parts of superfine zinc phosphate, 3~15 parts of ferrosilicon powder, 1~3 parts of zinc oxide powder, 3~10 parts of oxalate powder, 0.5~2 parts of sodium lignin sulfonate, Polyether-siloxane copolymer 0.1~0.4 parts, 25~65 parts of deionized water; In the sodium water glass solution, the mass fraction of sodium metasilicate is 10-40wt%, and the modulus of sodium metasilicate is 1-3.5; The particle size of the ultrafine zinc phosphate is 600-1000 mesh; The particle size of the ferrosilicon powder is 500-1000 mesh; The particle size of the zinc oxide powder is 500-1200 mesh; The particle size of the oxalate powder is 800-1200 mesh; The oxalate is one of aluminum oxalate, iron oxalate, magnesium oxalate and zinc oxalate; The specific formula of the B component is, in parts by weight: 80~140 parts of cement, 15~40 parts of sepiolite loaded curing agent, 3~10 parts of aluminum dihydrogen phosphate, 1~5 parts of polyhydroxy enhancer, Polyether-siloxane copolymer 0.1~0.4 parts, 55~110 parts of deionized water; The cement is ordinary Portland cement 42.5; The polyhydroxy enhancer is one of tris(2-hydroxyethyl)isocyanurate triacrylate and bis(hydroxyethyl)sulfone; The sepiolite-loaded curing agent is prepared by drying the sepiolite at 110-140°C for 2-5 hours, cooling the sepiolite to room temperature, and then placing the sepiolite in a completely dry and water-free vacuum-sealed impregnation kettle, continuously evacuating the kettle to maintain the pressure in the kettle at -0.096-0.1MPa, and maintaining the negative pressure for 20-30 hours. Then, the liquid amide is sucked into the reaction kettle by the negative pressure in the kettle, and the amount of liquid amide sucked is the minimum amount when all the sepiolite in the kettle is immersed. After reaching the minimum amount, the liquid amide is kept at a constant temperature in a sealed state for 24-30 hours. After 30 hours, the sepiolite in the kettle is transferred to a high-speed centrifuge for centrifugal separation, and the separated sepiolite is put into a clean impregnation kettle again, and then an aqueous solution of water-soluble silicon phosphate is added to the impregnation kettle, and the minimum amount added is to immerse all the sepiolite in the kettle. After standing and impregnating for 15 to 24 hours, stirring is started, and the stirring rate is controlled at 300 to 600 rpm. After stirring for 15 to 30 minutes, the sepiolite is continued to stand and impregnate for 15 to 24 hours, and then filtered and separated. The filtered solid is the sepiolite-loaded curing agent; The liquid amide is one of diethanolamide and formamide.
2. The ultra-durable double-liquid grouting material according to claim 1, characterized in that: The particle size of the sepiolite is 30-3000 nm; The aqueous solution of water-soluble silicon phosphate, wherein the mass fraction of water-soluble silicon phosphate is 15-30wt%.
3. The ultra-durable double-liquid grouting material according to claim 1, characterized in that: The preparation method of the component A is as follows: according to the specific formula of the component A in parts by weight, deionized water, sodium lignin sulfonate, polyether-siloxane copolymer, sodium water glass solution, ultrafine zinc phosphate, ferrosilicon powder, zinc oxide powder, and oxalate powder are placed in a high-speed stirring mixing kettle, the stirring rate is controlled to be 5000-9000 rpm, and after high-speed stirring and mixing for 14-20 hours, a mixed slurry is obtained, and after vacuum degassing, component A is obtained.
4. The ultra-durable double-liquid grouting material according to claim 1, characterized in that: The preparation method of the component B is as follows: according to the specific formula of the component B in parts by weight, deionized water, polyether-siloxane copolymer, polyhydroxy enhancer, aluminum dihydrogen phosphate, sepiolite-loaded curing agent, and cement are placed in a high-speed stirring mixing kettle, the stirring rate is controlled to be 6000-9500 rpm, and after high-speed stirring and mixing for 10-16 hours, a mixed slurry is obtained, and after vacuum degassing, component B is obtained.
Citation Information
Patent Citations
Double-liquid grouting material with good durability and no environment pollution
CN105272030A
Fly ash modified double-liquid grouting material
CN117800696A
Double-liquid slurry for surge blocking emergency rescue
CN115108781A
Ceramic tile paving dry-mixed mortar material special for decoration and preparation method thereof
CN116969743A